(3GdEfUGa ef GdcTGas - (3Yde GdOjf CHi ESMb YHO GdcQje Hf Ydj Hf YeQ GdYQGbis; (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s ((3LGeY GdCRgQ s)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdYdGeI Yde GdeMbbjf ENJUQJ ai gPG GdcJGH GdEfJUGa ef GdcTGa JUfja fGUQ GdOjf CMeO GdeGdci hMPaJ efg s
(3BNQgG (B:s
(3bGd CMeO hai GdJNUjU LQi Ydi YGOI GdESJYWGa aEfg eYg CJe hGddg YR hLd CYde Je GdcJGH GdeHGQc s
(3GdfSNI HgG MhGTs
(3hgh GNJUGQ cJGH GdGfJUGa ef GdcTGa dfGUQ GdOjf CMeO GdeGdci GdTgjQ HGHf GdefjQs
(3fSNI fajSI LOkG s
(3cJHJ ai MjGI GdeDda HBNQgG ELGRI HNW GdeDda HSeGY fGSN GdfSNI Ydjg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B186 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B402s
Keywords: (3GdJaSjQ hYdhe GdbQBfs